Transcendental Communication of Traditional Custodian in the Kecak Ramayana Performing Arts in Uluwatu Bali - Robby Hidajat; Pujiyanto; EW. Suprihatin DP; Muhammad ‘Afaf Hasyimy; Allfa Andranica Devya Aprilyawati; Adinda Nur Ramadhani Haris; Syamsul Hirdi Bin Muhid (Perspektif: Jurnal Ilmu-ilmu Sosial)
This article is the result of research on the transcendental communication of traditional leader in the Kecak Ramayana performance art in Uluwatu Bali. Traditional Custodian are Hindu religious leaders who are included in the presentation of the Kecak Ramayana. This customary leader does not exist in the new play of the Ramayana story. But his role is very important because he works outside and backstage. The purpose of this study is to reveal spiritual communication carried out by Traditional Custodian in the performance of the Kecak Ramayana dance in Uluwatu. This research method uses qualitative discrete. Data collection techniques used interviews with 4 sources, direct observation when the show was in progress, and retrieval of documentation to strengthen verbal data. The theories used in this research are ritual communication theory, non-verbal communication theory, and transcendental communication theory. The results of the study show patterns of spiritual communication that are customary stakeholders, namely (1) customary stakeholders as a link between the dimensions of the outer (profane) and inner (sacred) stages, (2) stakeholders carry out a reciprocal ritual, and (3) Traditional Custodian as a symbol of transcendental communication between the players, the audience, and Sang Hyang Widiwasa.